THE GODFATHER OF "OCCIDENTALITY": AUGUSTE COMTE AND THE IDEA OF "THE WEST". (August 2019) - VAROUXAKIS, GEORGIOS
Abstract : Recent theories concerning the origins of the idea of "the West" have missed the most important link in the story, the writings and tireless propagandizing efforts of Auguste Comte. It was Comte who first developed an explicit and elaborate idea of "the West" as a sociopolitical concept, basing it on a historical analysis of the development of the "vanguard" of humanity and proposing a detailed plan for the reorganization of that portion of the world, before it could serve the rest of humanity to achieve the same "positive" state of development. Previous authors who had used "the West" did not go beyond employing it casually and interchangeably with "Europe." Thus the modern political idea of "the West" was anything but an imperialistic project in its inception, despite widespread arguments in the literature that attribute its emergence to the needs of high imperialism. Comte's West was meant to abolish empires of conquest and establish world peace.